Knocking out Analysis of the CpxP gene using Crispr/Cas9 in Escherichia coli MG1655 - He, Xiaoliang (AMB Express, 2020)
Based on the analysis of cpxP genes among Escherichia coli strains, cpxP gene-targeting short guide RNA (sgRNA) was designed and inserted into the pGL3-MGP-RNA. The donor sequences (MG-HR) for homologous repair were designed and cloned by PCR. MG-HR and pGL3-MGP-RNA were transformed into E. coli MG1655 (pCas9). The cpxP gene expression cassette was amplified by PCR and subcloned into pBBR1MCS-2. Then the pBBR-cpxP was independently transformed into E. coli MG1655. The results of motility experiment suggest that cpxP gene had a significant effect on the movement ability of E. coli strain. The CpxP protein had a significant inhibition of bacterial activity. The lastest 81 CpxP proteins sequences were selected and analyzed by multi-sequence alignment and molecular cluster. The CpxP proteins were roughly divided into three categories. Our results suggest that the CpxP protein was involved in bacterial motility, infection and pathogenicity.